COVID-19 and missed or delayed vaccination in 26 middle- and high-income countries: An observational survey. Issue 6 (7th February 2022) - Shapiro, Gilla K.; Gottfredson, Nisha; Leask, Julie; Wiley, Kerrie; Ganter-Restrepo, Francine E.; Jones, Sarah P.; Menning, Lisa; Brewer, Noel T.
Abstract: Background: The COVID-19 pandemic has disrupted vaccination services and raised the risk of a global resurgence of preventable diseases. We assessed the extent of and reasons for missed or delayed vaccinations (hereafter 'missed') in middle- and high-income countries in the early months of the pandemic. Methods: From May to June 2020, participants completed an online survey on missed vaccination. Analyses separated missed childhood and adult vaccination in middle-and high-income countries. Results: Respondents were 28, 429 adults from 26 middle- and high-income countries. Overall, 9% of households had missed a vaccine, and 13% were unsure. More households in middle- than high-income countries reported missed childhood vaccination (7.6% vs. 3.0%) and missed adult vaccination (9.6% vs. 3.4%, both p < .05). Correlates of missed childhood vaccination in middle-income countries included COVID-19 risk factors (respiratory and cardiovascular diseases), younger age, male sex, employment, psychological distress, larger household size, and more children. In high-income countries, correlates of missed childhood vaccination also included immunosuppressive conditions, but did not include sex or household size. Fewer correlates were associated with missed adult vaccination other than COVID-19 risk factors and psychological distress. Common reasons for missed vaccinations were worry about getting COVID-19 at the vaccination clinic (15%) or when leaving the house (11%). Other reasons included no healthcare provider recommendation, clinic closure, and wanting to save services for others. Interpretation: Missed vaccination was common and more prevalent in middle- than high-income countries. Missed vaccination could be mitigated by emphasizing COVID-19 safety measures in vaccination clinics, ensuring free and accessible immunization, and clear healthcare provider recommendations.